The Pathless Seas: Configuring Displacement in British Romanticism - Katrina O’Loughlin (Ler História, 2021)
Mary Shelley’s Frankenstein (1818) narrativizes exile and displacement by enacting these thematically and formally at almost every level of the text. Exploring human movement and the possibility of human community, it constitutes Shelley’s response not only to her personal circumstances, but also to a Europe riven by twenty-three years of war. This essay considers the novel’s philosophical project of hospitality and friendship through the movements of Victor Frankenstein and his “Creature”, tracking their attempts to forge social and emotional bonds in the face of successive displacements from family, nation, and humanity generally. This article is part of the special theme section on Mobility and Displacement in and around the Mediterranean: A Historical Approach, guest-edited by Cátia Antunes and Giedrė Blažytė.